Comparison of the General Health of Parents of Hearing-Impaired Children with Early and Late Intervention - Nasrin Gohari; Seyede Faranak Emami; Bahareh Khavarghazalani (Shiraz University of Medical Sciences, 2023)
Background: Late identification and intervention of hearing loss in children negatively impact their hearing, language, and cognitive skills. Parents of hearing-impaired children (HIC) often experience high stress levels and depression. Therefore, this study aims to examine the effect of early intervention on the general health of parents of HIC.Method: A comparative cross-sectional study was conducted with parents of moderate to severe HIC who received either early or late intervention. The General Health Questionnaire (GHQ-28), which measures four subscales of physical symptoms, anxiety, social dysfunction, and depression, was administered to both groups of parents. The independent t-test, analysis of variance, and the Tukey test were employed to compare general health and its subscales between the two groups.Results: A significant difference (Pv = 0.042) was found between the overall general health scores of parents (both fathers and mothers) of HIC with early interventions and parents of HIC with late interventions, particularly on the social dysfunction subscale (Pv = 0.003). Mothers of children with late interventions exhibited a greater disturbance on the GHQ's social dysfunction subscale than other parents (Pv < 0.05).Conclusion: Early intervention improves the general health of HIC's parents, especially in the social dysfunction subscale. However, late intervention appears to have a more pronounced impact on the general health and social function of HIC mothers than other parents.